The Godfather II - Coppola, Francis Ford (Paramount Pictures, 1974)
Continuing saga of the Corleone family as they move to Nevada and make the casino business their major income source under the leadership of the increasingly paranoid and malevolent Michael, whose reign as the 'Don' is juxtaposed against the parallel tale of his father's escape from Sicily as a young boy and his subsequent rise to power in New York's Lower East Side during the turn-of-the-century.